Recent efficient strategies for improving the moisture stability of perovskite solar cells. Issue 30 (21st July 2017) - Li, Faming; Liu, Mingzhen
Abstract : Current popular and efficient strategies to improve the long-term stability regarding protection against moisture in the field of PSCs. Abstract : In the past few years, hybrid organic–inorganic perovskite solar cells (PSCs) have attracted much attention due to their excellent photovoltaic performance and extremely low fabrication costs. The power conversion efficiency (PCEs) of these PSCs has lepts from 3.8% to a verified PCE of 22.1% within just 7 years. However, the limited long-term stability of PSCs still restricts them from industrial applications, and furthermore, chemical decomposition in humid environments has been recognized as a main degradation pathway of perovskite materials. Although encapsulation techniques are usually used in the field of organic photovoltaics to slow down the degradation of organic materials, the key to resolving the degradation issues related to PSCs is to find stable perovskite materials or device architectures capable of achieving long-term stability. This review discusses the current popular strategies for enhancing the stability of PSCs, which are mostly, in general, concerned with modifying the properties of either the perovskite material itself or the charge transport layers. The stability of perovskite materials is usually optimized by compositional engineering with halides and cations. Meanwhile, on the other hand, incorporating inorganic charge transport layers or an interfacial moisture-resistant agent into PSCs are also considered as effective routes to sustain the device stability as well as to retain the performance of PSCs. This review systemically summarizes the recent efficient strategies for improving the long-term stability of PSC devices and provides useful suggestions for further developments in PSC stability.